Impact study electro processing irrigation water and the solution on growth and development of plants - Kovalenko, L.; Kovalenko, A. (Energy and Automation, 2015)
In this paper, the experimental study of influence of electrophysical water treatment and nutrient solutions on growth and development of plants, reasoned modes magnetic treatment and processing in the field of corona discharge of irrigation water and nutrient solution in a greenhouse.